Voxel-based analysis of diffusion tensor imaging in patients with mesial temporal lobe epilepsy - Sanches, Patrícia [UNESP]; Fujisao, Elaine Keiko; Braga, Aline M.S.; Cristaldo, Nathalia Raquel; dos Reis, Roberto [UNESP]; Yamashita, Seizo [UNESP]; Betting, Luiz Eduardo (Elsevier, 2017)
Purpose Quantitative techniques of diffusion analysis allow for an in-vivo investigation of the physiopathology of epilepsies. The objective of this study was to evaluate the variation of the main diffusion parameters and explore differences between two methodologies of voxel-wise analysis comparing a group of patients with mesial temporal lobe epilepsy (MTLE) with controls. Methods 24 patients with a diagnosis of MTLE were selected. All patients and a control group of 36 individuals were submitted to 3 T magnetic resonance imaging. Diffusion parameters were obtained from the raw images. Based on the tensors, a customized template was created, and images were registered into standard space. Voxel-based comparisons between patients and controls was performed by whole brain voxel-wise analysis and tract-based spatial statistics (TBSS). Tract-specific analysis (TSA) was performed in the mostly damaged fasciculi. Results 10 patients presented with right hippocampal sclerosis (HS), 11 with left HS and 3 with bilateral HS with left predominance. Whole brain voxel-wise analysis showed abnormalities mainly localized in the temporal lobes (total volume of 3859 mm3). TBSS showed more widespread abnormalities (21931 mm3). TSA pointed to abnormalities situated essentially in the temporal stem topography. Fractional anisotropy (FA) and radial diffusivity (RD) were the parameters that showed more abnormalities. Conclusion Whole brain voxel-wise analysis was more restricted than TBSS. The methods were complementary stressing the significance of the findings. The abnormalities were more frequently observed in FA and RD indicating the need for using several diffusion parameters for the investigation of patients with MTLE.
Keywords: Diffusion tensor imaging; Hippocampal sclerosis; Neuroimaging; Temporal lobe epilepsy